Assessment of Maximum Bite Force in Oral Submucous Fibrosis Patients: A Preliminary Study - Santosh Rayagouda Patil; G. Maragathavalli; D. N. S. V. Ramesh; Sheeja Vargheese; Ibrahim A. Al-Zoubi; Mohammad Khursheed Alam (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the maximum bite force (MBF) in oral submucous fibrosis (OSMF) patients and to compare them with that of healthy subjects. Material and Methods: Twenty patients who were clinically confirmed, as OSMF and 20 healthy controls matched for age, gender, and number of intact functional teeth were included in this study. For each subject, age, gender, weight, height and body mass index (BMI) were recorded. The MBF registration was carried out by the two evaluators, who were previously calibrated. Bite force was measured in the first molar region using a force transducer occlusal force meter for each subject seated at the upright position, with Frankfort's plane nearly parallel to the floor, and no head support. The Student's independent t-test was used to determine the statistical significance in relation to mean height, weight, BMI and the presence of number of intact teeth and MBF between the healthy subjects and OSMF individuals. A comparison of grades of OSMF with all variables was carried out by one-way ANOVA test. Results: No significant difference was found in mean age, mean height, weight, BMI and the presence of the number of intact teeth between healthy individuals and OSMF patients. The mean MBF in healthy subjects was 628.23 ± 24.39 N and 635.47 ± 31.22 N in OSMF patients. Even though the healthy subjects reported a higher MBF than OSMF patients did, the difference was statistically non-significant. With regards to sides, no significant difference was observed in mean MBF in healthy subjects and OSMF patients on the right (p=0.7818) and left side (p=0.6154). Conclusion: The healthy subjects reported higher MBF values than OSMF patients did and the difference was statistically non-significant.